MID-PERMIAN (KUBERGANDIAN-MURGABIAN) BIVALVES FROM THE KHUFF FORMATION, OMAN: IMPLICATIONS FOR WORLD EVENTS AND CORRELATION (Rivista italiana di Paleontologia e Stratigrafia, 1999)
Ten species, of which six are newly recognized, from ten genera, Nuculopsis, Phestia, Edmondia, Dyasmya, Janeia ?, Liebia ?, Vnigripecten, Cyrtorostra, Schizodus and Astartella ?, are described from the basal part of the Khuff Formation. Some forms apparently related to Dyasmya are discussed, the characters of Janeia and the classification of the aviculopectinids. The fauna has a special significance because it is associated with a major mid-Permian transgressive unconformity found in the Middle East and many other parts of the world. Because the transgression succeeds a major regression which is widely represented by hiatus or non-marine deposits, the fauna contributes significantly to understanding the world correlation of the time. An important world-wide change in fauna also takes place. The fauna from the lower part of the Khuff is regarded as not older than Kubergandian or its equivalent (Roadian and "Upper" Ufimian = Sheshminsk) but from the bivalves alone might range from Kubergandian to Murgabian or it’s probable equivalent the Kazanian.